Disturbance, diversity and phytoplankton production in a reservoir affected by inter-basin water transfers - Fornarelli, R.; Antenucci, J.; Marti, Clelia (Springer, 2013)
The effect of water transfers between two reservoirs on the phytoplankton community of the receiving reservoir was investigated over a 9-year period. Canonical correspondence analysis was used to demonstrate the significance of water transfers as an anthropogenic disturbance to the phytoplankton community and its diversity. A mass balance associated with a Granger causality test was applied to discriminate between the cell transport effect from the upstream reservoir and internal processes within the receiving reservoir, and to quantify the net phytoplankton growth in the receiving reservoir. Low and high disturbance regimes were identified and diversity was maximised during low disturbance conditions. The decrease of diversity during high disturbance conditions was explained by decreasing retention time, increasing silica loads and by the transport of specific phytoplankton genera, i. e. diatoms, from the upstream reservoir. Disturbance regimes significantly affected the relationship between phytoplankton production and diversity. Low disturbance regimes were described by phytoplankton dynamics likely influenced by complementarity effects, while high disturbance regimes were characterised by a phytoplankton community dominated by highly productive species and increased productivity, thus indicating an advantage of selection behaviour over complementarity effects. The phytoplankton diversity, expressed as evenness, was identified as a key variable explaining the relationship disturbance-diversity-phytoplankton production. © 2012 Springer Science+Business Media Dordrecht.